The Forests of Bombay State - Kaikini, N. S. (Indian Forester, 1954)
This article deals briefly with the historical background of forest management in Bombay State and the composition of the main forest growth and its extent, productivity and value are covered. The different methods of regeneration employed and the silvicultural problems encountered and the manner in which they are overcome is dealt with, giving their position of the management of forests through Working Plans. The extension of forestry to non-forest areas and its place in soil conservation programme is indicated. The advances in Wildlife Preservation and the unique development of Forest Labourers’ Cooperative Societies receive a bird’s eye view.